Gross morphological and morphometric study of the upper respiratory system of the African giant rat (Cricetomys gambianus, Waterhouse 1840). Issue 6 (23rd September 2021) - Ogbonnaya, Obioma; Ibe, Chikera Samuel; Ikpegbu, Ekele
Abstract: The nose is a structurally and functionally complex organ in the upper respiratory tract. It not only serves as the principal organ for the sense of smell, but also functions to efficiently filter, warm, and humidify inhaled air before the air enters the more delicate distal tracheobronchial airways and alveolar parenchyma of the lungs. Despite the volume of published studies on the biology of rodents, there is no information on the gross upper respiratory morphology of the African giant rat (AGR) in the available literature. Hence, this study aimed to examine the anatomy of the turbinates, their meatuses, and the morphometry of the nasal cavity. The following were found and reported in this study: (a) There were three nasal conchae in AGR: the nasoturbinate, which was the largest; the ethmoturbinate, which was composed of one well‐developed ectoturbinate and three well‐developed endoturbinates; and the maxilloturbinate, which was fusiform, short, and branched. (b) Three major meatuses were observed: the dorsal nasal meatus, which was the longest and widest; the middle nasal meatus, which was without limbs but had a deep oval caudal recess; and the ventral nasal meatus, which directly continued caudally into the nasopharyngeal meatus. (c) Four ethmoturbinates with four slit‐like meatuses were observed, each with dorsal and ventral limbs; the first contacted the middle nasal meatus but not the nasopharyngeal meatus. (d) There were three paranasal sinuses: one sphenoid, two frontal, and two palatine sinuses. The data obtained are relevant to pathologists and eco‐morphologists, considering the burrowing habitat and behaviors of AGR, and provide baseline data for more investigative studies.